Factors and Impacts of Major Selection on Mechanical Engineering Students in Vocational High School - Ibnu Ardiyanto; Khoiruh Huda; Kriswanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The phenomenon of mismatch between the chosen major and students’ interests in vocational education has become an important issue because it has the potential to affect the learning process and students’ psychological conditions. This study aims to examine the factors that influence the selection of majors as well as their impact on students’ learning engagement and psychological conditions. This research uses a descriptive qualitative approach with a case study design. The research subjects consist of eleventh-grade students of the Mechanical Engineering major selected purposively, as well as supporting informants, namely guidance and counseling teachers and the head of the major. Data were collected through in-depth interviews, observation, and documentation using interview guidelines as the main instrument. Data analysis was conducted using an interactive model through the stages of data reduction, data display, and conclusion drawing with triangulation techniques to ensure data validity. The results of the study show that the selection of majors is influenced by internal factors in the form of interest, motivation, and self-confidence, as well as external factors such as a grade-based admission system, family economic conditions, and parental encouragement, which indicate that external factors tend to be more dominant than internal factors in shaping students’ decisions in choosing the Mechanical Engineering major. The mismatch between majors and interests has an impact on low learning engagement, academic difficulties, as well as the emergence of stress and doubts about the future. These findings imply the need to strengthen career guidance services and to develop more adaptive placement systems in order to minimize the risk of major–student mismatch.